Etiology and Anatomical Location of Uveitis—Prognostic Factors for Disease Course and Laterality - Vesela Todorova Mitkova-Hristova; Marin Anguelov Atanassov (Life, 2025)
Background: Uveitis encompasses a broad group of diseases with infectious and non-infectious etiologies, potentially leading to permanent and irreversible visual impairment. This study aimed to determine whether the etiology and anatomical location of uveitis influence the course and laterality of the disease. Methods: This retrospective observational study included patients with uveitis treated at the University Eye Clinic of “St. George” University Hospital in Plovdiv, Bulgaria, between January 2011 and December 2023. All participants underwent a comprehensive eye examination and minimal laboratory screening, with additional tests and specialist consultations performed when necessary. Uveitis cases were categorized into anterior, intermediate, posterior, and panuveitis according to anatomical location; unilateral or bilateral according to laterality; and acute, chronic, or recurrent based on disease course. Results: The study included 606 patients aged between 3 and 87 years. The etiology and anatomical location of uveitis were significantly associated with the course and laterality of the disease (p < 0.001). Anterior and posterior uveitis were mostly unilateral, with a defined cause and characterized by acute or recurring progression. Intermediate uveitis was mostly idiopathic and chronic, while panuveitis had a more uniform distribution regarding disease progression. Among cases with a determined etiology, HLA-B27-associated uveitis was the most common (32.5%), characterized by sequential involvement of both eyes and a recurrent course. Viral and toxoplasmic uveitis were more frequently unilateral. Conclusions: Our findings indicate that the etiology and anatomical location of uveitis can serve as prognostic factors for contralateral eye involvement and the progression of the inflammatory process. We found that anterior and posterior uveitis were predominantly unilateral and typically presented with an acute or recurrent course, whereas intermediate uveitis and panuveitis were more commonly chronic. In men, uveitis more often had an acute onset, while in women, it tended to follow a chronic course.